2007
DOI: 10.1590/s0102-09352007000500019
|View full text |Cite
|
Sign up to set email alerts
|

Camallanus maculatus n. sp. (Nematoda: Camallanidae) in an ornamental fish Xiphophorus maculatus (Osteichthyes: Poeciliidae) cultivated in São Paulo State, Brazil

Abstract: The present study describes Camallanus maculatus n. sp. (Nematoda: Camallanidae) from Xiphophorus maculatus (Osteichthyes: Poecilidae) collected in an ornamental fish farm in São Paulo State, Brazil. Thirty-three out of 40 examined fish were parasitized (82% prevalence) with mean intensity of 2.8 (1-20). Male specimens were 3,500µm total length and females 7,100µm total length, provided with orange-brown buccal capsule and two developed tridents. Males showed two unequal spicules, gubernaculum absent and femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 9 publications
0
9
0
1
Order By: Relevance
“…On the other hand, the hosts of C. moraveci belong to the most frequently recorded hosts of C. cotti in aquarium conditions worldwide. Probably identical with C. cotti is also Camallanus maculatus Martins, Piazza et Garcia, 2004 reported from aquarium-reared Xiphophorus maculatus (Günther) in Brazil (Martins et al 2004), but since this species has not yet been formally described (per. comm.…”
Section: (C Lacustris C Oxycephalus C Truncatus)mentioning
confidence: 84%
“…On the other hand, the hosts of C. moraveci belong to the most frequently recorded hosts of C. cotti in aquarium conditions worldwide. Probably identical with C. cotti is also Camallanus maculatus Martins, Piazza et Garcia, 2004 reported from aquarium-reared Xiphophorus maculatus (Günther) in Brazil (Martins et al 2004), but since this species has not yet been formally described (per. comm.…”
Section: (C Lacustris C Oxycephalus C Truncatus)mentioning
confidence: 84%
“…They are common parasites found in fish, in both larval and adult stages (Martins et al, 2007). In ornamental fish, they may cause little damage to the host (Portz et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of the nematodes Capillaria pterophylli (Moravec et al, 1987) and Capillaria ancistri (Moravec et al, 1987) was observed in Pterophyllum scalare (Lichtenstein, 1823) (Moravec et al, 1987). In São Paulo, Martins et al (2007) identified the parasite Camallanus maculatus n. sp. in Xiphophorus maculatus (Gunther, 1866).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas C. corderoi, a parasite mainly of P. trucha in Chile and Argentina, has the buccal capsule with dentigerous ridges (subgenus Zeylanema Yeh), both other species, parasites of osteoglossiform fishes in the Amazon River Basin, have smooth ridges in the capsule (nominotypical subgenus Camallanus); the latter differ from each other in conspicuously different lengths and shapes of the female tail. Recently, Martins et al (2007) described a new species, C. maculatus Martins, Garcia, Piazza and Ghiraldelli from the cultured ornamental fish Xiphophorus maculatus (Günther) in Brazil, but this is evidently a synonym of C. cotti, an Asian species now introduced into many countries of different continents, where it parasitizes many species of cultured and native fish species , Wu et al 2007). suggested this synonymy, but because the paper describing C. maculatus was not yet published at that time, they could not do it formally.…”
Section: Tridentatus Was Described Bymentioning
confidence: 99%